Pengaruh Profitabilitas, Solvabilitas, dan Opini Audit terhadap Audit Delay Dimoderasi oleh Ukuran Perusahaan - Rinny Meidiyustiani; Putri Febisianigrum (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
This study aimed to analyze the influence of profitability, solvency, and auditor's opinion set on audit delay, and to analyze the size of company in moderating the effect of profitability, solvency, and auditor's opinion set to audit delay. The population in this study is mining companies listed on Indonesia Stock Exchange period 2012-2017 with using purposive sampling technique and obtained a sample of study as many as 32 companies. The analysis has been carried out by using multiple regression analysis and moderated regression analysis. The result of this study show that the partial profitability has negative effect to audit delay, solvency and auditor’s opinion has not effect to audit delay, the size of company cannot moderate the effect of profitability set to the audit delay, solvency can moderate the effect of profitability set to the audit delay and auditor's opinion cannot moderate the effect of profitability set to the audit delay.